STATE ANXIETY AND ITS RELATION TO SCORING ACCURACY IN FUTSAL FOR FEMALE STUDENTS - Al-Shamkhi, Marwa Fahem Hadi; Zahra, Dr. Mahmoud Abdul Jalil Abdul (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
The study aimed to investigate state anxiety and its relation to scoring accuracy in futsal for female students. The researcher hypothesized the existence of a statistically significant correlation between state anxiety and scoring accuracy in futsal. The researcher, being a futsal instructor, observed that some students fail to score goals due to either the importance of the match, inadequate preparation, or psychological factors, including state anxiety, which affects the students on the field. Therefore, the researcher decided to study this problem and understand the extent of anxiety's impact on students during the performance of scoring skills in futsal. The descriptive method was used as it is appropriate for solving the research problem. The research population consisted of fourth-year female students, totaling 43 students. Several statistical methods (mean, standard deviation, Pearson correlation coefficient) were used to interpret the raw scores. The following key conclusions were reached: • A correlation was found between state anxiety and scoring performance in futsal for female students. • A correlation was found between state anxiety and scoring in futsal.